Effect of Alton Kopri Wastewater on Lesser-Zab Raw Water - Wali Ali Abdullah; Shuokr Qarani Aziz (Tikrit Journal of Engineering Sciences, 2018)
This work aimed to study the impact of Alton Kopri wastewater on the Lesser-Zab River water. Specifically, the study aimed to determine the impacts of the formed wastewater on the Lesser-Zab River using the mass balance principle (MBP) and provide appropriate solutions to this problem. Fresh samples from Alton Kopri wastewater and the Lesser-Zab River water were collected from February 2013 to September 2013. The samples were analyzed for temperature, pH, total alkalinity, total hardness, total acidity, chloride, turbidity, solids, dissolved oxygen, 5-day biochemical oxygen demand, and sulfate. Results presented graphically demonstrated that Alton Kopri wastewater can be classified as medium- to strong-type wastewater, whereas the Lesser-Zab River can be categorized as a moderately polluted river and moderately hard to hard water. The application of MBP revealed that Alton Kopri wastewater affected the Lesser-Zab River water; hence, appropriate solutions were outlined to minimize the impact of the former on the water resource and treatment of the latter.